2021
DOI: 10.48550/arxiv.2110.04876
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Erbium-Implanted Materials for Quantum Communication Applications

Paul Stevenson,
Christopher M Phenicie,
Isaiah Gray
et al.

Abstract: Erbium-doped materials can serve as spin-photon interfaces with optical transitions in the telecom C-band, making them an exciting class of materials for long-distance quantum communication. However, the spin and optical coherence times of Er 3+ ions are limited by currently available host materials, motivating the development of new Er 3+ -containing materials. Here, we demonstrate the use of ion implantation to efficiently screen prospective host candidates, and show that disorder introduced by ion implantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…The optical transitions of the latter can exhibit remarkable coherence of several ms in some host materials (Böttger et al, 2006), approaching the lifetime limit in suited resonators (Merkel et al, 2020;Ulanowski et al, 2021). However, owing to the ms-long lifetime of their telecom transition in all studied hosts (Böttger et al, 2006;Gritsch et al, 2021;Stevenson et al, 2021;Weiss et al, 2021), using single dopants in this platform requires resonators with large Purcell enhancement factors, which have only been demonstrated recently (Dibos et al, 2018;Merkel et al, 2020).…”
Section: B Experimental Platformsmentioning
confidence: 99%
“…The optical transitions of the latter can exhibit remarkable coherence of several ms in some host materials (Böttger et al, 2006), approaching the lifetime limit in suited resonators (Merkel et al, 2020;Ulanowski et al, 2021). However, owing to the ms-long lifetime of their telecom transition in all studied hosts (Böttger et al, 2006;Gritsch et al, 2021;Stevenson et al, 2021;Weiss et al, 2021), using single dopants in this platform requires resonators with large Purcell enhancement factors, which have only been demonstrated recently (Dibos et al, 2018;Merkel et al, 2020).…”
Section: B Experimental Platformsmentioning
confidence: 99%
“…In addition to ease of Si photonic integration-assessed by the ability to grow on Si and perform straightforward fabrication-there are a variety of additional considerations for a candidate material to serve as a high-quality host for Er 3+ such as a minimal or controlled level of background nuclear spins, a wide bandgap, the number of substitutional sites available, and site symmetries. [27][28][29] To that end, previous measurements have suggested that rutile TiO 2 would be a good host for erbium because of narrow optical and spin linewidths in implanted bulk crystals owing to the nonpolar symmetry of the substitutional erbium site and the low natural abundance of nuclear spins, respectively. 30 Furthermore, TiO 2 thin films can be grown on Si using a variety of deposition techniques, 31,32 are CMOS-compatible, and are amenable to standard fluorine-and chlorine-based dry etch chemistries for topdown device fabrication.…”
mentioning
confidence: 99%